2009
DOI: 10.2174/156720109787048258
|View full text |Cite
|
Sign up to set email alerts
|

Design, Optimization, Preparation and Evaluation of Dispersion Granules of Valsartan and Formulation into Tablets

Abstract: The objective of the present work undertaken was to enhance the solubility and dissolution rate of valsartan a poorly water soluble antihypertensive, by preparation of solid dispersion granules which would additionally allow easy compression into tablets. The dispersion granules were prepared using a hot melt granulation technique which involved preparation of a homogenous dispersion of valsartan in gelucire-50/13 melt, followed by its adsorption on to the surface of aeroperl-300pharma, an inert adsorbent. A t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(28 citation statements)
references
References 0 publications
1
27
0
Order By: Relevance
“…The SEM analysis of the samples was performed to investigate the surface morphology and homogeneity of surface of granules. The samples of optimized granules of IR and SR minitablets were sputter coated with gold at room temperature before examination to render the surface of particles electroconductive (Shrivastava et al, 2009). The SEM analysis of the granules was done by Jeol JSM-840 (Tokya, Japan) SEM.…”
Section: Characterization Of Granules and Minitabletsmentioning
confidence: 99%
“…The SEM analysis of the samples was performed to investigate the surface morphology and homogeneity of surface of granules. The samples of optimized granules of IR and SR minitablets were sputter coated with gold at room temperature before examination to render the surface of particles electroconductive (Shrivastava et al, 2009). The SEM analysis of the granules was done by Jeol JSM-840 (Tokya, Japan) SEM.…”
Section: Characterization Of Granules and Minitabletsmentioning
confidence: 99%
“…Several formulation approaches have already been employed such as inclusion complexes with cyclodextrin, solid dispersions, surfactants (5), lipidic excipients (6), and nanoparticles (7) to enhance the oral bioavailability of valsartan but yielded limited fruition due to their solubility enhancement characteristic alone (8). Lately, self-emulsifying drug delivery systems (SEDDS) are found to be highly promising technique to enhance the oral bioavailability of poorly watersoluble drugs by circumnavigation of the hepatic first-pass effect, metabolism by gut cytochrome-P450 family of isozymes, inhibition of P-gp efflux, protection of drug degradation in the gastric acidic environment and drug absorption through lymphatic pathways (9,10).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the semicrystalline drug was embedded in the hydrophilic carrier and its solid state properties changed to amorphous one [10]. Previous studies have reported that disappearance of the characteristic endothermic peaks of the valsartan dispersed in Gelucire 50/13 is due to melting of the drug in the matrix [13].…”
Section: Resultsmentioning
confidence: 99%